Exploring Psychiatrists' Provision Of Medicines Information To Patients. (1st April 2019) - Okoli, Unoma Nonye; Fletcher, Guy Henry; Pagarkar, Aalia; Akinwuntan, Olaoluwamide; Zaidi, Mariam; Griffiths, Oliver; Mchale, Caitlin; Parker, Caroline
Aims & Method: Effective Medicines Information Provision Has Been Shown To Improve Patients' Understanding of Their Medications. This Positively Affects Medication Adherence, Shared Decision-making and Patient Satisfaction. This Qualitative Study Aimed to Explore the Provision of Information About Medicines For Patients by Psychiatrists, and to Identify Ways to Improve This; Results: Three Themes Emerged That Influenced the Provision of Information About Medicines by Psychiatrists: (1) Utilisation of Resources; (2) Barriers To Utilisation; (3) Attitudes Towards Resources; Conclusions: in Total, 19 Drivers Were Identified As Influencing Provision Of Medicines Information. the Dual Pathway Theory of Resource Provision Further Describes the Relationship Between These Drivers. to Improve Provision of Medicines Information These Drivers Should Be Considered Alongside Decision-making Pathways Used. This Includes Ensuring Doctors are Aware of Their Responsibilities In Providing Patients with Information About Medicines Appropriate to Their Needs, And the Organisation Reducing the Perceived and Actual Barriers to Provision Of Medicines Information.